Avaliação da atividade antinociceptiva espinhal da toxina Tx3-4 do veneno da aranha Phoneutria nigriventer em camundongos - Juliana Figueira da Silva (2009)
Existing medicines for the treatment of pain are often associated withserious side effects and rapid development of tolerance, thus, there is a need for new, more selective molecules. The inhibition of voltage-gated calcium channels (VGCCs) in the dorsal horn of the spinal cord has been shown an important target, once the reduction of intracellular levels of calcium is a mechanism of nociceptive transmission modulation. The objective of the present study was to investigate the possible antinociceptive activity of the toxin Tx3-4, purified from Phoneutria nigriventers venom, since affinity for N-, P/Q and R-type VGCCs wasestablished and compares activity with the -conotoxins MVIIC and MVIIA. The phonotoxin was intratecally injected and demonstrate an antinociceptive effect in behavioral response and inflammatory nociceptive models. The Tx3-4 was able to inhibit formalin induced nociception both pre- and pos-treatment in inflammatory phase, but -conotoxin-MVIIA actuated only in pre-treatmen and -conotoxina-MVIIC only in pos-treatment. In addition, Tx3-4 inhibited behavioral response NMDA-induced and postoperative mechanical allodynia, and as so, ithas been more powerfull and effective in clinic model and did not affect the response induced by hot-plate, without disturbing the reflexes that areresponsible to protect the skin and body tissues. Furthermore, there was a rise of therapeutic potential in a central sensitization model, postoperative nociception, and Tx3-4 did not affect the motor coordination or motor locomotion when administered in naive animals. Thus, more studies are necessary to better clarify the mechanisms involved both, Tx3-4 toxins antinociceptive effect, and toxicity in mice.